Physiological and pathological roles of tissue plasminogen activator and its inhibitor neuroserpin in the nervous system - Lee, Tet Woo; Tsang, Vicky W. K.; Birch, Nigel P. (Frontiers in Cellular Neuroscience, 2015)
Although its roles in the vascular space are most well known, tissue plasminogen activator (tPA) is widely expressed in the developing and adult nervous system, where its activity is believed to be regulated by neuroserpin, a predominantly brain-specific member of the serpin family of protease inhibitors. In the normal physiological state, tPA has been shown to play roles in the development and plasticity of the nervous system. Ischemic damage, however, may lead to excess tPA activity in the brain and this is believed to contribute to neurodegeneration. In this article, we briefly review the physiological and pathological roles of tPA in the nervous system, which includes neuronal migration, axonal growth, synaptic plasticity, neuroprotection and neurodegeneration, as well as a contribution to neurological disease. We summarize the tPA’s multiple mechanisms of action and also highlight the contributions of the inhibitor neuroserpin to these processes.